(untitled) (KULT_online, 2018)
In Foucault’s Last Decade Stuart Elden portrays the intellectual history of the last ten years of Michel Foucault’s life. By referring to published and unpublished sources (some only newly available to the public) as well as the testimonies of friends and colleagues, he convincingly reconstructs the development from Discipline and Punish via biopolitics and governmentality to Foucault’s interest in sexuality and antique ethics. Centering on Foucault’s main works and courses at the Collège de France from 1974 to 1984, Elden brilliantly discusses key concepts at their first emergence and concisely traces their development in regard to the entirety of Foucault’s work. He also promptly discusses various issues that shaped Foucault’s work, intellectually and institutionally.